2013
DOI: 10.1371/journal.pone.0055702
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Motion Analysis in Patellar Tendon Reflex Assessment

Abstract: BackgroundThe deep tendon reflex assessments that are essential to the accurate diagnosis of neurological or neuromuscular disorders are conducted subjectively in clinical neurology. Our aim was to assess deep tendon reflexes objectively with a new reflex quantification method.Methodology/Principal FindingsThe present study used a motion analysis technique to collect quantitative measurements for both the input and output of normal patellar tendon reflex. Reflex responses were measured as knee angles. The pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Because of the scarcity of measurement tools that can quantitatively evaluate the DTR test, results such as these that assess the reliability and validity of the DTR test are very rare. In a recent paper, the reliability and validity of DTR data were verified through motion analysis of the patellar tendon reflex; variation in percussion speed and angle were also incorporated into that study 8 ) . Consistent with our study, the authors found that the amplitude of the response increased linearly in accordance with increased percussion angle, and a concomitant motion analysis confirmed the high reliability of the DTR data 8 ) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Because of the scarcity of measurement tools that can quantitatively evaluate the DTR test, results such as these that assess the reliability and validity of the DTR test are very rare. In a recent paper, the reliability and validity of DTR data were verified through motion analysis of the patellar tendon reflex; variation in percussion speed and angle were also incorporated into that study 8 ) . Consistent with our study, the authors found that the amplitude of the response increased linearly in accordance with increased percussion angle, and a concomitant motion analysis confirmed the high reliability of the DTR data 8 ) .…”
Section: Discussionmentioning
confidence: 98%
“…Many previous studies have sought to identify quantitative and objective measures for the DTR test 6 , 7 , 8 ) . Kuruoglu and Oh 6 ) conducted an electrophysiological study using an electric hammer as a more quantitative means of conducting the DTR test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through manually applied instrumented reflex hammers, the reflex response of the patellar tendon has been quantified by the force and torque features of the reflex response [3,4,22,23]. The reflex response has also been quantified through wired triaxial accelerometers and optical electronic systems [3,4,24,25,26,27]. Wireless accelerometer systems for quantifying reflex response possess clear advantages over these described sensor applications, such as simplified mounting and application, minimal mass encumbrance, and robust signal transmission without line of sight or tethering requirements [3,4,7,28].…”
Section: Sensor System Strategy For Quantifying Tendon Reflexesmentioning
confidence: 99%
“…incorporated an optical motion analysis system for quantifying the patellar tendon reflex response. Multiple forces settings for quantified reflex input were derived from a reflex hammer attached to a protractor [26,27]. During 2006, LeMoyne et al conducted a similar themed reflex modulation study.…”
Section: Introductionmentioning
confidence: 99%